Pengaruh Suhu dan Lama Penyangraian terhadap Karakteristik Fisik dan Mutu Sensori Kopi Arabika (Coffea arabica L) - Ni Putu Ayu Purnamayanti; Ida Bagus Putu Gunadnya; Gede Arda (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2017)
This research aimed to (1) determine the effects of roasting temperature and duration on the physical characteristics and sensory quality of Arabica coffee beans, and (2) determine the roasting temperature and duration that produce the best physical characteristics and sensory quality of Arabica coffee. The experiment was conducted using a factorial completely randomized design with two factors. The first factor was roasting temperature, consisting of three levels: 220°C, 235°C, and 250°C. The second factor was roasting duration, consisting of three levels: 14, 17, and 20 minutes. The variables observed in this study were yield, moisture content, color (CIELAB), acidity, and organoleptic properties. The results showed that roasting temperature and duration significantly affected yield, moisture content, color value, acidity level, aroma, taste, and color of Arabica roasted coffee. The roasting temperature of 235°C with a duration of 14 minutes was the best treatment, producing roasted coffee with the best physical characteristics and sensory quality, namely 82.5% yield, 1.08% (w/w) moisture content, 6.51 color value (Lightness), 5.84 acidity, aroma score of 3.6 (between moderate and like), taste score of 3.2 (between moderate and like), and color score of 3.6 (between moderate and like).